A glimpse into the psychological status of E.N.T inpatients in China: A cross‐sectional survey of three hospitals in different regions. Issue 2 (1st June 2019) - Tian, Jun; Li, Li; Tao, Chun‐Lei; Hao, Rong‐Ying; Huang, Fu‐Hui; Ge, Xiao‐Hui; Zhang, San‐Mei
Abstract : Objective: To determine whether E.N.T inpatients have a higher prevalence of mental illness than the general population and whether certain diseases are more likely to be associated with mental illness than other diseases. Methods: This cross‐sectional survey was conducted in the E.N.T departments of three hospitals in different cities in China. The psychological status of all consecutive adult inpatients was assessed within 1–2 days following hospital admission using the Symptom Checklist‐90 (SCL‐90), Zung Self‐Rating Depression Scale (SDS) and Zung Self‐Rating Anxiety Scale (SAS). Inpatients from the general surgery and pneumology departments at the same hospital were enrolled and surveyed as control groups. Results: The 439 patients enrolled in the final analysis accounted for 88.0% of all E.N.T inpatients during the study period. Of these patients, 16.4% were in an anxious state and 79.5% were in a depressive state. The overall anxiety (41.7 ± 9.7) and depression (55.9 ± 29.2) scores were much higher than Chinese norm (29.8 ± 10.0 and 33.5 ± 8.6, respectively), and significant differences were observed ( t  = 20.89, P  < 0.01 and t  = 13.12, P  < 0.01, respectively). Although 18.7% of the E.N.T patients were psychiatric distress, these patients scored lower on the SCL‐90 than the Chinese norm. Furthermore, the patients in the E.N.T department had a higher prevalence of anxiety and depression than those in the general surgery department but a similar prevalence to those in the respiratory department. Conclusion: Psychological distress, particularly anxiety and depression, are widespread in patients with otolaryngological diseases. Therefore, the identification and treatment of co‐occurring psychiatric disorders in this high risk and clinically challenging group of patients are urgent in China.